2015
DOI: 10.1002/tox.22178
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental consequences of gestational and lactational exposure to pyrethroids in rats

Abstract: Indiscriminate use of pyrethroids has raised serious health related concerns, especially about their effects on children. The present study was designed to assess the developmental neurotoxicity of two pyrethroids; bifenthrin (BIF) and β-cyfluthrin (CYF) administered at 1/15 of LD in rats. Pregnant females were exposed to the test compounds orally throughout gestation and lactation periods. Neonates were weighed and sexed at birth and were observed for any gross abnormality. Growth, viability and weaning indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…Gestational exposure to type I PIs alters brain vascular formation (Imanishi and others 2013), increases blood-brain barrier permeability (Sinha and others 2004), increases oxidative stress both shortly and long after the end of exposure (Sinha and others 2006), causes functional deficits in the cholinergic muscarinic system (Eriksson and Nordberg 1990), decreases monoamine levels and neocortical and hippocampal thicknesses during postnatal development (Imanishi and others 2013). These effects are accompanied by delayed physical and motor development, decreased locomotor activity, impaired motor coordination (Imanishi and others 2013; Syed and others 2015) and deficient learning and memory (Sinha and others 2006) even at adulthood.…”
Section: Pyrethroids (Pis)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational exposure to type I PIs alters brain vascular formation (Imanishi and others 2013), increases blood-brain barrier permeability (Sinha and others 2004), increases oxidative stress both shortly and long after the end of exposure (Sinha and others 2006), causes functional deficits in the cholinergic muscarinic system (Eriksson and Nordberg 1990), decreases monoamine levels and neocortical and hippocampal thicknesses during postnatal development (Imanishi and others 2013). These effects are accompanied by delayed physical and motor development, decreased locomotor activity, impaired motor coordination (Imanishi and others 2013; Syed and others 2015) and deficient learning and memory (Sinha and others 2006) even at adulthood.…”
Section: Pyrethroids (Pis)mentioning
confidence: 99%
“…Experimental studies in animal models demonstrate that gestational exposure to high doses of type II pyrethroids elicits severe effects such as increased resorptions and neonatal death, decreased brain regions weight and delayed physical and motor development in rodents (Husain and others 1992; Syed and others 2015). However, significant effects are also identified at low doses.…”
Section: Pyrethroids (Pis)mentioning
confidence: 99%
“…Pregnant dams treated with 10 mg kg -1 bw of deltamethrin showed transient neurotoxicity and weight loss, but no effect on testosterone synthesis was observed in their male offspring (171). Beta-cyfluthrin and bifenthrin affected behaviour in adult and neonate rats, which may be related to a drop in AChE activity and the elevated oxidative stress in their brains (172). Another study also showed that the blood-brain barrier of infant rats was more permeable to deltamethrin than that of older rats (173).…”
Section: Pyrethroid Effects On Non-target Vertebratesmentioning
confidence: 96%
“…The general PYR metabolite associated with exposures is 3phenoxybenzoic acid (3-PBA). There are also specific metabolites for α-Cypermethrin, cis/trans-3-(2,2-dichlorovinyl)-2,2-dimethylycyclopropanecarboxylic acid (cis/trans-DCCA), cis-3-(2,2-dibromovinyl)-2,2dimethylcyclopropane carboxylic acid (-DBCA) (cis-DBCA or DBCA), a deltamethrin specific metabolite; and 4-fluoro-3phenoxybenzoic acid (FPBA), a cyfluthrin specific metabolite (Bradberry et al, 2005a;Bradberry, et al, 2005b;Chen et al, 2015;Chuang et al, 2011;Clifton et al, 2013;Elflein et al, 2003a;Ellison et al, 2011;Haudenschild, et al, 2014;Heudorf, et al, 2006;Leng, et al, 2006;McKelvey, et al, 2013;Scollon, et al, 2009;Syed et al, 2015;Wolansky et al, 2008).…”
Section: Metabolismmentioning
confidence: 99%
“…PYRs are detoxified by rapid metabolized in the liver through two distinct pathways dependent on their structure, a cytochrome P450 catalyzed oxidation and hydrolysis catalyzed by esterases (Leng, et al, 2006;Miyamoto, 1976;Scollon, et al, 2009;Syed, et al, 2015;Wang, et al, 2016). Hydrolysis is the primary mode of PYR metabolism that occurs rapidly in the liver producing inactive metabolites in the urine.…”
Section: Pyrethroid and Organophosphate Metabolismmentioning
confidence: 99%